198 Effects of different dietary standardized ileal digestible lysine specifications on growth performance of grow-finish pigs. (30th November 2020) - Lu, Ning; Vier, Carine; Cast, Wayne; Orlando, Uislei; Hamilton, Dan; Van De Stroet, Denise; Spath, Isaiah; Hanson, Dan; Edler, Roy; Scholtz, Emily
Abstract: The objective was to determine the effects of different standardized ileal digestible (SID) lysine (Lys) specifications on performance of grow-finish pigs. A total of 2, 106 pigs (PIC 359×Camborough, initially 22.0±0.43 kg) were used in a 72-d growth trial with 27 pigs per pen and 13 pens per treatment in a randomized complete block design. Pigs were fed corn-soybean-meal-based diets in three phases from 22-41, 41-62, and 62-91 kg body weight (BW). Treatments consisted of low (L) or high (H) SID Lys in each phase: LLL (1.05, 0.88, and 0.73%); LLH (1.05, 0.88, and 0.82%); LHH (1.05, 0.99, and 0.82%); HLL (1.18, 0.88, and 0.73%); HHL (1.18, 0.99, and 0.73%); and HHH (1.18, 0.99, and 0.82%). Lysine curves from PIC2008 and PIC2016 nutrient specification manuals were used to estimate SID Lys levels for L or H diets, respectively. Data were analyzed using generalized linear mixed models with pen as the experimental unit. From 22-41 kg, feeding high Lys improved (P< 0.10) average daily gain (ADG), feed efficiency (G:F), and final BW compared to low Lys. From 22-62 kg, feeding HH Lys increased (P< 0.05) ADG compared feeding LL or HL Lys. Pigs fed HH Lys or LH Lys had improved (P< 0.05) G:F compared to those fed LL Lys. Pigs fed LH or HH Lys had greater (P< 0.05) final BW compared to pigs fed HL. Pigs fed HH Lys had greater (P< 0.05) feed intake compared to pigs fed HL. From 22-91 kg, there was no evidence for differences in ADG, feed intake, G:F, or final BW. In summary, pigs fed 1.18% SID Lys had improved ADG, G:F, and final BW compared to pigs fed 1.05% SID Lys from 22-41 kg. Feeding a range of Lys specifications resulted in similar growth performance from 22-91 kg.